IMPLIKASI KECERDASAN DALAM PEMBELAJARAN PAI di SD IT PERADABAN KOTA SERANG - Najmi, Najmi; Kholili, Ahmad; Dirjo, Dirjo; Maslihah, Maslihah (Fakultas Agama Islam Universitas Ibn Khaldun Bogor, 2023)
An effective learning process must pay attention to all aspects of intelligence possessed by students. For this reason, this study aims to reveal the involvement of intelligence in learning that must be considered by teachers in learning PAI at SD IT Civilization, so that the learning process can run according to the level of needs and abilities of students. Qualitative is the approach used in this research with the type of field study research to examine the data obtained at SD IT Civilization as the primary source and several relevant book sources as secondary data. Data collection technique used is interview. Based on data analysis through the stages of reduction, presentation and verification as well as drawing conclusions, the results of this research are to reveal the implications of intelligence in learning that must be applied by teachers by providing services to students who focus on multiple intelligences by providing learning process facilities that support the development of their intelligence. The conclusion of this study reveals that intelligence and learning are two elements that are definitely involved in the learning process, because someone can be smart if he learns and someone can learn if he uses his intelligence to the fullest. Therefore the role of the teacher is very vital in providing learning that is implicated by intelligence.